Vascular plant communities in Portugal (continental, the Azores and Madeira) - Costa, José C. (2012)
In this paper we propose a syntaxonomic scheme, according to the Code of Phytosociological Nomenclature for the vegetation of Portugal: continental and the Azores and Madeira archipelagos. The scheme encompasses 827 associations (4 communities), 245 alliances, 116 orders, and 64 vegetation classes. The 58 suballiances, 2 suborders and 4 subclasses, are also mentioned, as auxiliary ranks. For the higher syntaxa down to suballiance level, succinct ecological, physiognomic and chorological diagnosis has been made, and the characteristic species are related. New syntaxa names and corrections are described and listed in Annex I. It is also presented a floristic catalogue sheet with the syntaxonomic optimal for each taxon (Annex III). This list contains 2930 taxa.